A Müncheni Südost-Institut létrehozása és első éveinek magyar kapcsolatai - Orosz, László (Közép-Európai Közlemények, 2015)
If we take a look at the Horthy era’s Hungarian-German political science relations, at every turn we encounter endeavors of the Munich-based Südost-Institut, which was the most important institute specializing in research related to the so-called „Südostraum” region. Researching the history related to the institute’s formative years, we may come to the conclusion that through the early to mid-30’s, the Südost-Institut’s profile was less concerned with academic / research pursuits than with politically-driven undertakings, and as a result, the foundation was lacking to have referred to it credibly as an „academic institute”. We may cite as sufficient evidence either the institute’s network of predominantly „Völkisch” organizations, its population policy-themed lecture series, or even the preparatory courses and the information found in the associated materials and brochures, as well as their professional quality, wording, and target audience. The arrival of Fritz Valjavec at the institute (autumn 1935) would mark a definitive break, from which point there was not only a change in the institute’s personnel, but also a fundamental change in direction concerning research priorities, publication structure and international networking (mainly in the direction of the Danube region). Taken together, these justify our referring to a new era for the institute and southeastern research from the mid-30’s on.